The rationale of the sterling area : texts and commentary - Conan, A. R. (London : Macmillan : New York : St. Martin's Press, 1961)
The book examines the structure and working of the sterling system. It also shows the factors that determine the strength of sterling and their relationships.
Includes index
Includes bibliographic footnotes
usc 02/11/18
Loans
Keywords: Sterling area